Quantitative lipidomics reveals alterations in donkey milk lipids according to lactation. (25th April 2020) - Li, Mohan; Li, Weixuan; Wu, Junrui; Zheng, Yan; Shao, Junhua; Li, Qilong; Kang, Shimo; Zhang, Zhenghan; Yue, Xiqing; Yang, Mei
Highlights: We analyzed lipids in donkey colostrum (DC) and mature milk (DM). Thirteen subclasses of 335 lipids were identified in DC and DM. Sixty lipids were significantly different between DC and DM. The different lipids were involved in six metabolism pathways. Our results provided insight into alterations in donkey milk lipids during lactation. Abstract: The composition of donkey milk is similar to that of human milk. However, the lipid content in donkey milk is lower than that in human milk. Thus far, the lipid composition of donkey milk during lactation has not been well-studied. Through mass spectroscopy-based quantitative lipidomics, we analyzed lipids in donkey colostrum (DC) and mature milk (DM). Thirteen subclasses of 335 lipids were identified in both DC and DM; 60 lipids – 17 upregulated and 43 downregulated – were differentially regulated between DM and DC (Variable Importance in Projection >1, P  < 0.05), demonstrating that lipid composition changed with lactation. These different lipids were involved in 19 metabolic pathways, of which glycerophospholipid, linoleic acid, alpha-linolenic acid, glycosylphosphatidylinositol-anchor, glycerolipid, and arachidonic acid metabolism were the most relevant. Our results provide insights into quantitative alterations in donkey milk lipids during lactation, development of donkey milk products, and screening of potential biomarkers.